2016
DOI: 10.1016/j.nucengdes.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Transient behavior of ASTRID with a gas power conversion system

Abstract: The present article is dedicated to preliminary transient studies carried out for the analysis of the system overall behavior of the ASTRID (Advanced Sodium Technological Reactor for Industrial Demonstration) demonstrator developed in France by CEA and its industrial partners. ASTRID is foreseen to demonstrate the progress made in SFR technology at an industrial scale by qualifying innovative options, some of which still remain open in the areas requiring improvements, especially safety and operability. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…The Initiating Event (IE) induces a loss of the pumps associated to the RRA and RRC systems, which can not be employed (Tenchine, 2010); -The alternative procedure, proposed in this paper, substitutes the RRB system by the gas PCS in case of a LOOP. This strategy has preliminary been investigated (Bertrand et al, 2016b). First, it was demonstrated that even if the TM rotation speed decreases to zero (normal behaviour for a LOOP accident), the recuperator HX allows the PCS to conserve a low natural circulation of gas which slows the heating up of the core.…”
Section: Description Of the Two Loop Sequencesmentioning
confidence: 99%
“…The Initiating Event (IE) induces a loss of the pumps associated to the RRA and RRC systems, which can not be employed (Tenchine, 2010); -The alternative procedure, proposed in this paper, substitutes the RRB system by the gas PCS in case of a LOOP. This strategy has preliminary been investigated (Bertrand et al, 2016b). First, it was demonstrated that even if the TM rotation speed decreases to zero (normal behaviour for a LOOP accident), the recuperator HX allows the PCS to conserve a low natural circulation of gas which slows the heating up of the core.…”
Section: Description Of the Two Loop Sequencesmentioning
confidence: 99%
“…In some SFR concepts with Brayton cycles as power conversion systems, compressors determine the global cycle efficiency and their transient modeling is therefore essential (see Refs. Bertrand et al, 2016;Mauger et al, 2019). Finally, more and more safety or power generation concepts involve supercritical CO2 cycles.…”
Section: Introductionmentioning
confidence: 99%